Analisis Kuantitatif Expected Return dan Standar Deviasi (Kasus SIDO dan KLBF) - Dian Evelyn Naibaho; Nurhatta, Amelia; Neysa Adellia; Salwa Safitri Humairoh (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study analyzes the efficient performance of pharmaceutical stocks listed in the LQ45 index, specifically PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO) and PT Kalbe Farma Tbk (KLBF.JK), using the Markowitz Model. Data collected from 2020 to 2024 reveals distinct characteristics in expected return and investment risk between the two stocks. SIDO recorded an expected return of 0.0090 (0.9%) with a standard deviation of 0.0887 (8.87%), indicating higher return potential but accompanied by greater risk. Conversely, KLBF showed an expected return of 0.0044 (0.4%) and a standard deviation of 0.0509 (5.09%), suggesting lower risk but also lower return potential. The findings highlight that SIDO is an efficient choice for risk-seeking investors willing to tolerate higher volatility for greater returns. Meanwhile, KLBF is more suitable for risk-averse investors prioritizing stability. This study emphasizes the importance of understanding the relationship between expected return and risk in investment decision-making and provides insights into the application of the Markowitz Model in evaluating portfolio efficiency.